A Implementasi Ekonomi Syari'ah : Marketing Syari'ah: DIGITAL MARKETING PADA UMKM (STUDI KASUS DI DESA GEBANG KECAMATAN GEMUH) - mukarromah, vitayatul; Syarofi, Muhammad (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2025)
Digital Marketing Assistance for MSMEs in Gebang Village, Gemuh District, is an effort to improve the understanding and ability of business actors in marketing online. MSMEs as one of the pillars of the village economy often face obstacles in marketing according to standards. This is due to the lack of knowledge and skills in social media. Through this assistance, training and technical guidance are carried out on how to market MSMEs in a simple way, such as creating MSME content on social media. The methods used include socialization, workshops, and direct assistance to MSME actors. The results of this activity show a significant increase in the ability of MSME actors to market in a more structured and accountable way. The positive impact is the increased trust of business partners and consumers, as well as facilitating access. This activity is expected to be the first step in encouraging sustainable MSME growth in Gebang Village.